A Review on Advanced CRISPR-Based Genome-Editing Tools: Base Editing and Prime Editing - Saber Sichani, Ali; Ranjbar, Maryam; Baneshi, Maryam; Torabi Zadeh, Farid; Fallahi, Jafar (Molecular biotechnology, 2023)
In the field of medicine, it is axiomatic that the need of a precise gene-editing tool is critical to employ therapeutic approaches toward pathogenic mutations, occurring in human genome. Today we know that most of genetic defects are caused by single-base pair substitutions in genomic DNA. The ability to make practically any targeted substitutions of DNA sequences at specified regions in the human genome gives us the chance to employ gene therapy in most known diseases associated with genetic variants. In this regard, CRISPR/Cas9 applications is becoming more and more popular along with the significant advancements of life sciences, by employing this technology in genome-editing and high-throughput screenings. Several CRISPR/Cas-based mammalian cell gene-editing techniques have been developed during the last decade, including nucleases, base editors, and prime editors, all of which have the exact mechanism at first glance. However, they address a subset of known pathogenic sequence mutations using different methods. First, we highlight the development of CRISPR-based gene-editing tools. Then we describe their functions and summarize the conducted research studies, which are increasing the reliability of these strategies to better efficiencies for prospective gene therapies in the near future. Lastly, we compare the capabilities of all these platforms together besides their probable limitations. Graphical Abstract